2000
DOI: 10.4049/jimmunol.164.9.4826
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Functions of Brain Dendritic Cells Emerging During Chronic Infection of Mice withToxoplasma gondii

Abstract: During chronic infection of mice with Toxoplasma gondii, gene message for IL-12p40, CD86, and the potassium channel Kv1.3 was detected in brain mononuclear cells, suggesting the presence of dendritic cells (DC) in the CNS. Consistently, cells bearing the DC markers CD11c and 33D1 were localized at inflammatory sites in the infected brain. The number of isolated CD11c+ brain cells increased until peak inflammation. The cells exhibited the surface phenotype of myeloid DC by coexpressing 33D1 and F4/80, little DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 47 publications
3
131
1
1
Order By: Relevance
“…In experimental infectious and autoimmune diseases, subpopulations of CNS-DC were shown to be derived from microglia [26,27]. This is in contrast to our observations, in which we found that almost all the DC in intracranial GL261 tumors are derived from donor BM cells (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In experimental infectious and autoimmune diseases, subpopulations of CNS-DC were shown to be derived from microglia [26,27]. This is in contrast to our observations, in which we found that almost all the DC in intracranial GL261 tumors are derived from donor BM cells (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…2). It has been shown that DC recruited to the CNS during autoimmune or infectious diseases may originate from microglial cells [26,27]. In order to address whether intracranial TIDC originate from CNS-resident precursors and would thus differ from subcutaneous TIDC in their origin, intracranial and subcutaneous TIDC from CD45-congenic BM chimeric mice were studied.…”
mentioning
confidence: 99%
“…59 Cells displaying immunoreactivity towards markers of dendritic cells have been observed in several experimental brain inflammatory conditions. 12,[50][51][52][53][54][55][56][57][58] In addition, the phenomenon of epitope spreading 59,60 also suggests that, once brain inflammation occurs, new antigens being released from the brain during inflammatory processes can stimulate additional immune responses. However, evidence against antigens released from the brain causing autoimmune diseases is strong, and includes the lack of autoimmunity following stroke, brain surgery, brain tumors, and brain infarcts.…”
Section: Inflammation and Adaptive Immune Responses To Adenoviral Vecmentioning
confidence: 99%
“…The presence of dendritic cells within the brain ventricles, choroid plexus, and meninges, together with lymphatics present within these structures, could represent the cellular basis for these effects. [52][53][54]56,61 Long-term transgene expression, in the presence of transitory inflammation, and in the absence of priming of either a humoral or cellular immune response, can be achieved in the brain. In other organs, this remains more difficult, since they contain, even in the resting stage, professional antigen-presenting cells with migratory properties, as well as lymphatics channels.…”
Section: Inflammation and Adaptive Immune Responses To Adenoviral Vecmentioning
confidence: 99%
“…The first to describe DC in the CNS were Matyszak and Perry who detected the NK-T-and DC-restricted OX62 antigen in brains of rats with experimental autoimmune encephalomyelitis (EAE) [8]. Whereas CD11c + DC isolated from the CNS of mice with cerebral toxoplasmosis were sown to be potent antigen presenting cells [9], no functional data are available on DC appearing in the CNS during the course of an autoimmune response such as that seen in EAE.…”
Section: Introductionmentioning
confidence: 99%